Effects of PET Fibers on Pumpability, Shootability, and Mechanical Properties of Wet-Mix Shotcrete - Xiangfei Cui; Guoming Liu; Cheng-long Wang; Yudong Qi (Advances in Civil Engineering)
Polyethylene terephthalate (PET) fiber from waste plastic bottles is an environmentally friendly fiber that can improve the mechanical properties of wet-mix shotcrete. The main objective of this paper is to investigate the effects of PET fiber parameters on pumpability, shootability, and mechanical properties of wet-mix shotcrete. For this purpose, the orthogonal test based on three factors and three levels was conducted. The width, length, and content of PET fiber were selected as the experimental variables. The tests of wet-mix shotcrete reinforced by PET fibers were carried out, along with properties tests such as slump, pressure drop, build-up thickness, compressive strength, and splitting strength. The results showed the change trend of shotcrete performances with increasing PET fiber parameters (width, length, and content). According to the orthogonal test, PET fiber parameters were determined (1 mm width, 20 mm length, and 5 kg/m3 content). Furthermore, relationships between slump and pumpability and shootability were explored, as well as the relationships between pumpability, shootability, and mechanical properties. It was found that pressure drop and compressive strength had the strongest negative linear relationship among all fitting relationships. We hoped that this study could contribute the useful information for the application of wet-mix shotcrete mixed with PET fibers.